Adjustment of Shy Adolescents in Relation to their Social Intelligence at Secondary Level of Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The present study was focus on adjustment ability among shy adolescents’ students in relation to their social intelligence. The sample consists of 200 undergraduate students with 100 boys and 100 girls, which were selected randomly from different secondary schools of five districts of Jharkhand. Adjustment Inventory and Social Intelligence Inventory are used to collect the data from the shy adolescent students. Product moment correlation and t-test statistical techniques were employed. The study revealed that male and female shy students of secondary level of education did not differ significantly with regards to their adjustment ability, however, differ significantly with differently social intelligent persons.